PENERAPAN MODEL PEMBELAJARAN TGT DISERTAI MOTIVASI BELAJAR MENINGKATKAN HASIL BELAJAR SENI RUPA SISWA SMA ADABIAH PADANG - Nilawati, Dr. Yahya, M.Pd., Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2018)
The aim of this research is to determine the effect of Team Game  Tournament learning model and learning motivation on student learning  outcomes in art learning at SMA Adabiah Padang. This research using  quantitative type of quasi experiment by 2x2 factorial design. Data collection  techniques used are learning motivation instrument and learning outcomes  test instrument. The result of first hypothesis points tcount= 4,361 and  ttable= 2,045 at alpha level = 0,05, these represent that tcount > ttable ,  then Hi is accepted. Second hypothesis points tcount= 4,037 and ttable=  2,306 at alpha level = 0,05, these represents that tcount > ttable , then Hi is  accepted. Third hypothesis points tcount= 2,319 and ttable= 2,306 at alpha  level = 0,05, these represent that tcount > ttable , then Hi is accepted. The  conclusion according the result of the research obtained that the application of TGT model and learning motivation could to increase the learning outcomes of students in art learning at SMA Adabiah Padang.Keyword: Team Game Tournament learning model, learning motivation, learning outcomes, visual arts.